Optimasi Sistem Transportasi Perkotaan untuk Mereduksi Kemacetan Menggunakan Model Simulasi Lalu lintas - Said, Lambang Basri; Saraswati , Rizki Ayu (Syntax Corporation, 2025)
Traffic congestion is a significant problem that is often faced by major cities around the world, including Makassar, which not only affects travel efficiency, but also negatively impacts the environment and the quality of life of residents; This study aims to optimize the urban transportation system by developing a computer-based traffic simulation model that is able to analyze and take into account various variables that contribute to congestion, such as traffic volume, vehicle movement patterns, and road geometry, where field data shows that the traffic volume at peak hours reaches 4200 smp/hour, with 65% of vehicles consisting of cars and motorcycles, the average speed of vehicles ranges from 15-20 km/h, the waiting time increases by 3 minutes when congestion occurs, CO2 emissions increase by 5 tons/day, and the level of Urip Sumoharjo road service which results in LOS E values and travel times increase by 10 minutes due to congestion; The results of this analysis are expected to provide valuable insights into the effectiveness of various transportation system optimization scenarios, including traffic signal adjustment, traffic direction regulation, and the addition of special lanes for specific vehicles, so as to reduce congestion and improve the efficiency of the overall urban transportation system, which is ultimately expected to improve the quality of life of Makassar residents and create a better environment sustainable for future generations.